Abrogation of Gap Junctional Communication in ES Cells Results in a Disruption of Primitive Endoderm Formation in Embryoid Bodies. (20th December 2016) - Wörsdörfer, Philipp; Bosen, Felicitas; Gebhardt, Martina; Russ, Nicole; Zimmermann, Katrin; Komla Kessie, David; Sekaran, Thileepan; Egert, Angela; Ergün, Süleyman; Schorle, Hubert; Pfeifer, Alexander; Edenhofer, Frank; et al.
Abstract : Gap junctional intercellular communication (GJIC) has been suggested to be involved in early embryonic development but the actual functional role remained elusive. Connexin (Cx) 43 and Cx45 are co-expressed in embryonic stem (ES) cells, form gap junctions and are considered to exhibit adhesive function and/or to contribute to the establishment of defined communication compartments. Here, we describe the generation of Cx43/Cx45-double deficient mouse ES cells to achieve almost complete breakdown of GJIC. Cre-loxP induced deletion of both, Cx43 and Cx45, results in a block of differentiation in embryoid bodies (EBs) without affecting pluripotency marker expression and proliferation in ES cells. We demonstrate that GJIC-incompetent ES cells fail to form primitive endoderm in EB cultures, representing the inductive key step of further differentiation events. Lentiviral overexpression of either Cx43 or Cx45 in Cx43/45 mutants rescued the observed phenotype, confirming the specificity and indicating a partially redundant function of both connexins. Upon differentiation GJIC-incompetent ES cells exhibit a strikingly altered subcellular localization pattern of the transcription factor NFATc3. Control EBs exhibit significantly more activated NFATc3 in cellular nuclei than mutant EBs suggesting that Cx-mediated communication is needed for synchronized NFAT activation to induce orchestrated primitive endoderm formation. Moreover, pharmacological inhibition of NFATc3 activation by Cyclosporin A, a well-described inhibitor of calcineurin, phenocopies the loss of GJIC in control cells.